Growing in character : values education series 9 - Argana, Janet R.; Pasa, Nathalie A. (Quezon City. Brilliant Creations Publishing, Inc., 2018)
"This textbook focuses on the seven core values: health and harmony with the environment; sustainable development; nationalism and engagement towards world solidarity; love and compassion; truth and integrity; and peace and justice. The contents of the series spiral from (a) the realization of oneself and one's own value systems and goals; (b) to the development of social skills necessary for one's interaction with his immediate environment; (c) to the firming up one's positive outlook towards work, in order to nurture productive indivduals who are ready to take their place in society."
Includes glossary and bibliography.
English text
Keywords: Values education -- Study and teaching